Evaluation of Nurses’ Readiness at the Puskesbun Clinic of PTPN IV Langkat in Managing Medical Emergencies among Plantation Workers - Ridwanul Hakim Harsya; Rahmad Gurusinga; Basyariah Lubis (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Medical emergencies represent a significant occupational health risk frequently encountered by plantation workers due to the physically demanding nature of their work, the use of work equipment, and exposure to specific environmental conditions. Nurses’ readiness in managing emergency situations is strongly influenced by their level of knowledge, first aid skills, and the availability of healthcare service support. Therefore, this study aimed to examine the readiness of nurses in plantation clinics in dealing with medical emergencies by considering the existing clinical service support. This study employed a qualitative design with a thematic approach and was conducted at the Puskesbun Clinic of PTPN IV Langkat. The research informants consisted of plantation workers, clinic healthcare personnel, and clinic managers selected through purposive sampling. Data were collected through in-depth interviews, field observations, and document reviews. Data analysis was carried out using thematic analysis, which included data reduction, data display, and conclusion drawing. The findings indicated that most nurses in plantation clinics possess basic readiness in identifying medical emergency conditions; however, their first aid skills remain limited. Clinical service support plays a significant role in enhancing nurses’ readiness, particularly through the availability of healthcare personnel, initial emergency care services, and medical referral systems. The identified challenges include limited emergency training for nurses, inadequate facilities and infrastructure, and long distances and travel time to referral healthcare facilities. In conclusion, the readiness of nurses in plantation clinics to manage medical emergencies is not yet optimal and requires further improvement through continuous training, enhancement of clinical facilities, and the development of more effective referral coordination systems.